International Tax Reform, Digitalization, and Developing Economies - Clavey, Colin; Pemberton, Jonathan Leigh; Loeprick, Jan; Verhoeven, Marinus (World Bank, Washington, DC, 2019)
While significant progress has been made in international tax cooperation, the interests of developing economies require greater priority and attention. This paper considers policy options that are currently under consideration in different international fora, drawing on the WBG's work in supporting tax policy and administration reforms in developing economies. The overall direction of the reform debate is promising and could shift taxing rights towards market jurisdictions, as well as strengthen the tools available to deter profit shifting to low-taxed entities. Some of the proposals under discussion could be adopted in the near-term but need to be better tailored to developing economy needs. This paper identifies five areas for improvement. First, the proposals relating to the allocation of global non-routine profits need to be simplified and incorporate more formulaic approaches. Second, work on the allocation of taxing rights should include in its scope the option to reallocate all non-routine profit, rather than only that part reflecting user value or marketing intangibles. Third, the (income inclusion) idea of targeting lowly taxed profits is sound, but it needs to be a tool for both capital importing and exporting countries. Fourth, detailed guidance is needed on the use of withholding tax as an efficient collection mechanism for source jurisdictions and on the application of mandatory safe harbors with an arm’s length let out. These tools can help ensure efficient administration in developing economies. And, fifth, effective administration requires appropriate access to information. Practical limitations to accessing relevant information for developing economies need to be removed. This should include an amendment to current standards allowing jurisdictions to impose robust domestic filing obligations for CBCR (and/or similar future additional reporting obligations).